Periodic flow due to oscillations of eccentric rotating porous disks - Ersoy, H. Volkan (SAGE PUBLICATIONS LTD, 2015)
This article is concerned with the periodic flow induced by non-torsional oscillations of two porous disks rotating about distinct axes. While the porous disks are initially rotating with the same angular velocity about non-coincident axes, they start to execute non-torsional oscillations in their own planes and in the opposite directions. An analytical solution corresponding to the velocity field in the periodic state is obtained. The variations in the components of the horizontal force per unit area exerted by the fluid on the top and bottom disks with the time are investigated for the suction/injection velocity parameter, the Reynolds number, the ratio of the frequency of oscillation to the angular velocity of the disks, and the dimensionless velocity amplitudes of oscillation. It is shown that the horizontal force on the upper disk is not equal to that on the lower disk.
Keywords: Newtonian fluid; orthogonal rheometer; porous disk; non-torsional oscillation; periodic flow; NON-TORSIONAL OSCILLATIONS; UNSTEADY-FLOW; NONCOAXIAL ROTATIONS; CONCENTRIC ROTATION; FLUID; INFINITY; Thermodynamics; Engineering